Metastatic Breast Cancer Presenting as Fulminant Hepatic Failure: A Case Report and Literature Review - Malcolm S. Trimble; Cameron N. Ghent; David R. Grant; Caroline A. McLean (Canadian Journal of Gastroenterology)
A case of metastatic breast carcinoma presenting as fatal fulminant hepatic failure is presented. The patient did not have previously diagnosed breast cancer and presented with ascites, Jaundice, abdominal pain, nausea, vomiting and hepatic encephalopathy. She died within four weeks of the onset. Seven similar cases previously reported are reviewed. Metastatic carcinoma should he considered in the differential diagnosis of fulminant hepatic failure.